FILM “KEHORMATAN DI BALIK KERUDUNG” SEBAGAI LIVING AL-QURAN ( Perspektif Gender) - Ahmad Muttaqin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
The film,“Kehormatan di Balik Kerudung” (read: KdBK) is a religious Indonesian film containing gender issues.In relation to this, it is necessary to view this movie as livingAl- Quranphenomenon. By using femenism approach, this paper concludes that first, the“KdBK” movie contains gender issue as reception from Q.S. Ali ‘Imran (3): 132. Second, many gender imbalance issues are showed from this movienamely, discrimination, stereotype, subordination, marginal issue and double burden.